A checklist of wild mushroom diversity and distribution in the Jahangirnagar University campus area, Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2023)
This comprehensive study focuses on a checklist survey of wild mushrooms and documents their morphological variability and diversity at Jahangirnagar University, a natural and social forest area in Bangladesh. Through field studies on the campus grounds from June to October 2021, 60 samples were collected from which 40 species were identified by morphological characters, belonging to 33 genera, 26 families, and 10 orders. Most species were identified from the order Agaricales and the highest frequency (83.33%) from the orders Polyporales and Agaricales. The highest species abundance was 83.33% for Ganoderma spp., Crepidotus applanatus and the density was 70% for Marasmiellus candidus. The dominant species were Ganoderma spp., Coprinus disseminates, Marasmius spp., Schizophyllum commune, Calvulina coralloides. The wild mushrooms were prevalent in the natural forest areas of the Jahangirnagar University campus. As far as we are aware, this report is the very first work on wild mushrooms or macro-fungi on the campus of Jahangirnagar University. This survey shows that the campus grounds are enriched with a wide variety of wild mushrooms.Jahangirnagar University J. Biol. Sci. 11(1 & 2): 41-67, 2022 (June & December)